2017
DOI: 10.1111/awr.12120
|View full text |Cite
|
Sign up to set email alerts
|

Encountering Work: Intergenerational Informality, Child Labor, and Malnutrition in Urban Ecuador

Abstract: This article examines the interconnections among informality, child labor, and child malnutrition in households at the bottom of the socioeconomic pyramid in urban Ecuador. Through qualitative interviews with 120 adult informal laborers, mostly street vendors, I elicited stories that not only revealed current labor conditions but also reflected upon whole lives engaged in informal work. Interviews uncovered lifelong structural conditions that perpetuate the social and economic inheritances of intergenerational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Thirteen sources were selected for full-text review [15,16,[21][22][23][24][25][26][27][28][29][30][31]. The contextual factors were categorized using the four-layer model (Figure 2), adapted from the 'rainbow' model [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen sources were selected for full-text review [15,16,[21][22][23][24][25][26][27][28][29][30][31]. The contextual factors were categorized using the four-layer model (Figure 2), adapted from the 'rainbow' model [19].…”
Section: Resultsmentioning
confidence: 99%
“…When defining the concept, they usually cited one of Singer's works [8,32]. One article [30] defined a syndemic by focusing especially on the adverse contextual factors that facilitate the emergence and exacerbation of multiple health conditions. Only two articles provided no explicit definition of a syndemic [26,29], but the authors' rationale and citations made it clear that they were well aware of the concept and its meaning.…”
Section: Conceptualizing Syndemicsmentioning
confidence: 99%
“…Similarly, a study found that children who 'encounter work' by simply being with their families working in informal sector market jobs in Quito, Ecuador, also tended to live in informal settlements on the outskirts of town and have extended commutes to get to workplaces around the city (Hinrichsen 2017). This study did not specifically look at WFCL, but it noted that even the common experience of spending time in informal sector markets and working with family led to significant detrimental health effects and the perpetuation of poverty and marginalisation, locking children into informal work as adults.…”
Section: Spatial Dynamics and Wfclmentioning
confidence: 99%
“…Furthermore, in part because Western white hegemonic norms preclude the economic participation of children (Zhao, ), the economic contributions of children in bioarchaeology are often overlooked (Alfonso‐Durruty & Thompson, ). Ethnographic evidence, however, suggests a variety of conceptions of child agency and vulnerability across social groups (Bugarin, ; Hinrichsen, ; Stephens, ; Zarger & Stepp, ).…”
Section: Introductionmentioning
confidence: 99%